Transport medicine, osteochondrosis, diagnostic, preventions of complications, physiotherapy, impulse magnetic stimulation - Loboiko, V. V. (Journal of Education, Health and Sport, 2017)
Loboiko V. V. The use of pulsed magnetic stimulation system of medical rehabilitation of patients with degenerative disorders of the spine in railway employees. Journal of Education, Health and Sport. 2017;7(1):396-407. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.290604 http://ojs.ukw.edu.pl/index.php/johs/article/view/4259 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017. UDK 611.711-612.394.2 The use of pulsed magnetic stimulation system of medical rehabilitation of patients with degenerative disorders of the spine in railway employees V. V. Loboiko The Ukrainian scientific and research institute of medical rehabilitation and balneology of the Ministry of health of Ukraine Sanatorium “Belaya Acacia”, Оdesa belaja_akacia@ukr.net Summary Offered us medical and rehabilitation complex using pulsed magnetic stimulation for the prevention and treatment of complications of destructive-degenerative disorders of the spine in patients with low back pain lumbar zone greatly increases the effectiveness sanogenetic mechanisms to improve trophic processes in the spinal segments, both in the area of formation of pathological disorders and in areas distal lower extremities. The positive dynamics of functioning structures spinal nerve under the influence of pulsed magnetic stimulation provides improved hemodynamic performance throughout the vascular bed in the lower extremities. It was established that the basis sanogenetic improve the mechanisms of blood vessels, are processes that define their tone, elasticity and adequacy of response to treatment and rehabilitation influence factors. High efficiency pulsed magnetic stimulation achieved by potentiating its effect on biological effects, which are formed in the body using standard treatments for osteoarthritis. Key words. Transport medicine, osteochondrosis, diagnostic, preventions of complications, physiotherapy, impulse magnetic stimulation.